Preparasi dan Karakterisasi Sediaan Solid Lipid Nanoparticle (SLN) Gliklazid - ANISA AMALIA; MAHDI JUFRI; EFFIONORA ANWAR (Fakultas Farmasi Universitas Pancasila, 2015)
Solid lipid nanoparticle (SLN) has been proposed as colloidal carriers using solid lipid as matrix material. In this study, gliclazide-loaded solid lipid nanoparticle has been prepared with high shear homogenization and freeze drying method using stearic acid as lipid material, Tween 80 and PEG 400 as surfactant, ethanol as`co-solvent and lactose as cryoprotectant. Characterization was performed on SLN dosage from before and after freeze drying, which includes the analysis of particle size, zeta potential value, morphology analysis and entrapment efficiency of gliclazide. Results indicated gliclazidecan be formulated in SLN dosage form using high shear homogenization and freeze drying method. The morphology study revealed that the prepared SLN were irregular in shape with mean particle size of 878.0 ± 246.3 nm and 745.8 ± 204.0 nm. Zeta potensial values of gliclazide-loaded SLN were found –